The pricing of secured non-performing loans: lessons from an internship - Barros, Patrícia Santos Pereira de (2020)
The present document refers to a study conducted at Arrow Global Group - White Star Asset Solutions (WS), in the form of an internship. The subject was the pricing of secured Non-performing loans (NPL), in particular, the time to recover debt. The methodology selected was to follow a statistical approach, recurring to external and internal data to elaborate estimations. In particular, external factors such as macroeconomics, judicial procedures, civil law and court type are considered in the analysis, and the parameters, that were part of the time matrix in use, are revisited from a different perspective to compile a new time matrix. Relying on this time matrix one can predict the debt recovery moment, which has a direct influence on the pricing of the portfolios under management by WS. This is an important topic since it is at the core of WS’ activities. At a more general level, the work undertaken during the internship is valuable to the investment community at large. In particular, investors operating in this market seek to acquire portfolios with a good recovery percentage and high return on investment. The methodology employed and the results uncovered seem to suggest that the new time matrix, that was developed, may help achieve these two objectives.